Little Red Riding Hood = Caperucita roja - Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Estrada, Pau (San Francisco, Calif. : Chronicle Books, 1999)
A little girl meets a hungry wolf in the forest while on her way to visit her sick grandmother.
Accelerated Reader
Text in English and Spanish.
Keywords: Fairy tales; Folklore -- Germany -- Juvenile literature; Spanish language materials -- Bilingual -- Juvenile literature